2014
DOI: 10.1124/jpet.113.210203
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 4 Activation Constricts the Human Bronchus via the Release of Cysteinyl Leukotrienes

Abstract: Prior studies have demonstrated that the ion channel transient receptor potential vanilloid 4 (TRPV4) is functionally expressed in airway smooth muscle cells and that TRPV4 single nucleotide polymorphisms are associated with airflow obstruction in patients with chronic obstructive pulmonary disease. We sought to use isometric tension measurements in ex vivo airways to determine whether short-term pharmacological activation of TRPV4 with thewould constrict human bronchial tissue. As predicted, transient recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 23 publications
(40 reference statements)
4
36
1
Order By: Relevance
“…The value presented in the human ciliary NPE cells was one order of magnitude lower that obtained in the cerebrospinal fluid barrier protection carried out by TRPV4 (EC 50 34 nM) (Narita et al, 2015). The value presented in the present manuscript was also lower than the obtained when measuring the human bronchus constriction (EC 50 10 nM) (McAlexander et al, 2014).…”
Section: Introductioncontrasting
confidence: 70%
“…The value presented in the human ciliary NPE cells was one order of magnitude lower that obtained in the cerebrospinal fluid barrier protection carried out by TRPV4 (EC 50 34 nM) (Narita et al, 2015). The value presented in the present manuscript was also lower than the obtained when measuring the human bronchus constriction (EC 50 10 nM) (McAlexander et al, 2014).…”
Section: Introductioncontrasting
confidence: 70%
“…TRPV4 is expressed across a wide range of non-neuronal human cell types in the airways, including structural cells such as airway smooth muscle, epithelial cells, fibroblasts and pulmonary vessels and inflammatory cells including macrophages (but not highly differentiated surrogates: the circulating monocytic precursor cell, monocyte derived macrophages, in vitro differentiated promonocytic THP-1 and U937 cells or promyelocytic HL-60 leukaemia cells), neutrophils and T-cells [99,107,111,112,114,[128][129][130][131][132]. However, in the respiratory system, the function of TRPV4 is probably best understood in relation to its role in acute lung injury, which is not covered in this review [133].…”
Section: Trpv4mentioning
confidence: 99%
“…Consistent with this are observations that a TRPV4 agonist can evoke a mast-cell dependent contractile response of human bronchi and guinea pig tracheal airway smooth muscle in vitro. This effect is thought to be mediated by TRPV4-mediated ATP release from airway smooth muscle, which activates P2X4 receptors on mast cells to release cysteinyl leukotrienes (LT) which activate the Cys LT 1 receptor to evoke contraction [112,134]. Interestingly, many of the functional effects of TRPV4 activation are due to the release of ATP and activation of purinoceptors [8,82,99,134,135] and TRPV4-induced ATP release has been demonstrated in human macrophages, epithelial and smooth muscle cells [99,113,135].…”
Section: Trpv4mentioning
confidence: 99%
“…However, it has been suggested that TRPV4 does cause cough via a different mechanism to that seen with TRPA1 and TRPV1 ). In addition, activation of TRPV4 has been shown to cause contraction of both human and animal airway smooth muscle (Jia et al 2004;McAlexander et al 2014). Therefore, a TRPV4 antagonist could prove to be an attractive target for lung disease to combat both bronchoconstriction and cough and could be used alongside a TRPA1 or TRPV1 antagonist to target a different population of airway afferent fibres.…”
Section: Trpv4 Antagonists In the Clinicmentioning
confidence: 99%